2014
DOI: 10.1038/srep06792
|View full text |Cite
|
Sign up to set email alerts
|

Reversible switching of in-plane polarized ferroelectric domains in BaTiO3(001) with very low energy electrons

Abstract: The switchable bipolar ground state is at the heart of research into ferroelectrics for future, low-energy electronics. Polarization switching by an applied field is a complex phenomenon which depends on the initial domain ordering, defect concentration, electrical boundary conditions and charge screening. Injected free charge may also to be used to reversibly switch in-plane polarized domains. We show that the interaction between the initial domain order and the bulk screening provided by very low energy elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Controlled polarisation switching has even been demonstrated with MEM. 207 Finally, very recent studies have shown that domain walls can controllably be injected at desired positions, 208 with the abilty to reproducibly and reversibly engineer multiple walls. 209 Thus, the emerging role of ferroelectric domain walls as nanoelectronic components in the past few years suggests that PFM will play a key role towards domain-wall-based nanocircuit development.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled polarisation switching has even been demonstrated with MEM. 207 Finally, very recent studies have shown that domain walls can controllably be injected at desired positions, 208 with the abilty to reproducibly and reversibly engineer multiple walls. 209 Thus, the emerging role of ferroelectric domain walls as nanoelectronic components in the past few years suggests that PFM will play a key role towards domain-wall-based nanocircuit development.…”
Section: Discussionmentioning
confidence: 99%
“…For both electrical and mechanical switching, ferroelastic switching seems to occur most readily at the highly active tips of ferroelastic needle domains. Such switching of ferroelastic domains in ferroelectric BaTiO 3 was observed in low energy electron microscope (LEEM) experiments [29]. Electric switching of 90 degree domains in BaTiO 3 follows the same patterns as purely ferroelastic switching [30].…”
Section: Introductionmentioning
confidence: 63%
“…Thus, superconductor materials represent an opportunity worthy of consideration for the implementation of tunable photonic crystals with remarkable applications as optical filters, reflectors, switches and sensing devices, and tunable resonators 31 36 , among others. On the other hand, ferroelectric thin films feature significant technological aspects such as short response time 37 , remanent polarization 38 , faster tuning compared to ferromagnetic materials 39 , smaller and lighter structures 40 , high power capacity 41 , and Pockels modulation 42 , which make of BTO a suitable material for developing high-performance electro-optical modulators 43 , 44 , photodetectors 45 , and novel devices such as, non-volatile optical memories 46 , 47 . In particular, the latter could serve in a wide range of applications, such as a high-speed optical buffer memory by means of the high broadband of optical fibers, with a significant reduction of power consumption for data processing.…”
Section: Introductionmentioning
confidence: 99%